The Theoretical and Analytical Framework of Dynamic Capabilities in IT Flexibility: An Exploratory Study in The Oil Products Distribution Company - MIJBAS, Hayder Abdulmohsin; ISLAM , Muhummad KHAIRUL; KHUDARI , Mohamed (Journal of Ecohumanism, 2025)
Businesses are growing interested in using IT to gain a sustainable competitive advantage in today’s rapidly changing business environment. This involves developing dynamic capabilities that enable them to stand out and take the lead in their industry. The current research is focused on evaluating the level of interest among the research sample participants in dynamic capabilities and their dimensions (such as reconfiguration capabilities, sensing capabilities, seizing capabilities, and learning capabilities) and their influence on IT flexibility. The results of the statistics analysis to the hypotheses of influence showed a significant effect of dynamic capabilities at the aggregate level and the dimensions level in information technology’s flexibility. This research indicates that the dynamic capabilities and flexibility of information technology and its construction guide organisations to ensure their continuity, survival, and growth and to invest in opportunities and face challenges by focusing on practical cooperation and constructive cognitive participation in completing work and solving problems.